THE INFLUENCE OF ADVERTISING AND DISCOUNTS ON GOFOOD APPLICATIONS ON CONSUMER PURCHASES IN BOGOR CITY - Hasnin, Hannisa Rahmaniar; Megawati, Dewi; Riany, Desmy; Maulani, Denia (Manager : Jurnal Ilmu Manajemen, 2023)
Advertising and discounts are part of marketing techniques that are commonly used by companies to attract consumers and encourage them to make purchases. The purpose of this study was to measure how much influence advertising and discounts have on consumer purchasing decisions. The research is quantitative method, with data collection by distributing questionnaires online via Google forms in the Bogor area which collected 100 respondents. The research was analyzed through statistical techniques of correlation analysis, descriptive statistics and regression analysis using SPSS 27. Analysis using the t test and F test showed that the independent variables of Advertising and Discounts on the dependent variable of consumer purchases had a significant effect both partially and simultaneously in influencing decisions consumer purchases. The results of the multiple regression analysis are Y = 6.561 + 0.405X1 + 0.439X2. The R Square value shows that Advertising and Discounts have a contribution in increasing product purchasing decisions in the GoFood application by 43%. There are other factors that have not been studied at 57% which can support an increase in consumer purchases such as personal selling, publicity and direct marketing.